1923 N.D. Laws 381 - (:unkn) unknown (My University, 1923)
Ch. 266, § 9.: Selling to Minors. Any person or persons who shall sell, barter, hire, lend or give to any minor under the age of eighteen years any pistol or revolver shall be deemed guilty of a misdemeanor, and shall upon conviction thereof be fined not less than $100, nor more than $1,000, or be imprisoned not less than three months, nor more than one year, or both.
Keywords: TRANSFER - MINORS